Stability of blood-based biomarkers of Alzheimer's disease over multiple freeze-thaw cycles - Keshavan, Ashvini (Alzheimers Dement (Amst), 2018)
INTRODUCTION: Freeze-thaw instability may contribute to preanalytical variation in blood-based biomarker studies. We investigated the effects of up to four freeze-thaw cycles on single molecule array immunoassays of serum neurofilament light chain and plasma total tau, amyloid β 1–40 (Aß(40)), and Aβ 1–42 (Aβ(42)). METHODS: Individuals who had peripheral venepuncture during investigation of suspected neurodegenerative disease were recruited. After standardized preprocessing, 200 μL of plasma and serum aliquots were stored at −80°C within 60 minutes. Aliquots underwent one to four freeze-thaw cycles. RESULTS: There was no significant difference across four freeze-thaw cycles for serum neurofilament light chain (n = 12), plasma total tau (n = 11), or plasma Aβ(42) (n = 12). For plasma Aβ(40) (n = 14), there were significant median reductions by ratios of .96 and .92 at the third and fourth cycles, respectively. DISCUSSION: Up to four freeze-thaw cycles do not influence single molecule array blood biomarkers of neurofilament light chain, total tau, or Aβ(42), with at most minor reductions in Aβ(40).